2018
DOI: 10.1002/ieam.4040
|View full text |Cite
|
Sign up to set email alerts
|

Transformation/dissolution characterization of tungsten and tungsten compounds for aquatic hazard classification

Abstract: The transformation/dissolution protocol (T/DP) for metals and sparingly soluble metal compounds was applied to determine the transformation/dissolution (T/D) characteristics of yellow tungsten trioxide, WO ; blue tungsten oxide, WOx, x taken as 2.9; tungsten disulphide, WS ; tungsten metal, W; 3 samples of tungsten carbide, WC; sodium tungstate, Na WO · 2H O; ammonium paratungstate (APT), (NH ) (H W O ) · 4H O; and ammonium metatungstate (AMT) (NH ) (H W O ) · 3H O. The T/D data were used to derive aquatic haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This, together with an assessment of degradability, allows us to derive the environmental hazard classification. This approach has been successfully applied to derive environmental hazard classifications on metal concentrates, mattes, alloys, metal powders, massive metals, and metal compounds (Skeaff et al 2008(Skeaff et al , 2011(Skeaff et al , 2012Skeaff and Beaudoin 2014;Huntsman et al 2018).…”
Section: Field and Laboratory Studies On The Fate Of Metal Ions In Aq...mentioning
confidence: 99%
“…This, together with an assessment of degradability, allows us to derive the environmental hazard classification. This approach has been successfully applied to derive environmental hazard classifications on metal concentrates, mattes, alloys, metal powders, massive metals, and metal compounds (Skeaff et al 2008(Skeaff et al , 2011(Skeaff et al , 2012Skeaff and Beaudoin 2014;Huntsman et al 2018).…”
Section: Field and Laboratory Studies On The Fate Of Metal Ions In Aq...mentioning
confidence: 99%
“…Previous studies (Skeaff et al 2008(Skeaff et al , 2011Skeaff and Beaudoin 2014;Huntsman 2018) have demonstrated that properly equipped and operated laboratories can apply the T/DP to metal-bearing substances to yield acute and chronic aquatic hazard classification outcomes that are reliable, consistent, and in agreement with other laboratories. In the development of the T/DP-E, it was therefore important to maintain as many elements of the original T/DP as possible.…”
Section: Discussionmentioning
confidence: 71%
“…The T/DP has been included in the United Nations Globally Harmonized System (GHS) as Annex 10 (United Nations 2017). The T/DP has been successfully applied to derive hazard classifications on a wide range of metal-bearing substances including metals, metal compounds, mattes, alloys, and concentrates (Skeaff et al 2008(Skeaff et al , 2011Skeaff and Beaudoin 2014;Huntsman et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…tungsten carbide and tungsten alloys) may also become airborne, later to settle in soils and surface waters. Once settled, the W-bearing particles may leach and enter soil porewaters and surface waters, although the amount of leaching is dependent on the solubility and stability of the particle (Huntsman et al, 2018). Treated wastewater (not necessarily exclusive to mining, milling, and smelting operations) may also contain elevated tungsten concentrations, particularly in waters with alkaline pH.…”
Section: Anthropogenic Sources Of Tungsten To the Environmentmentioning
confidence: 99%